2021
DOI: 10.1002/adom.202100400
|View full text |Cite
|
Sign up to set email alerts
|

Deep Silicon Amorphization Induced by Femtosecond Laser Pulses up to the Mid‐Infrared

Abstract: Direct laser writing of amorphous lines in crystalline silicon has the potential for becoming a flexible alternative to silicon‐on‐insulator technology for photonic integrated circuits. Yet, the maximum amorphous layer thickness achieved is 60 nm, which is below the requirements for waveguiding at telecom wavelengths. Here, the authors report on different strategies to push the layer thickness beyond today's limit. To this end, irradiation with femtosecond laser pulses covering an extremely broad wavelength ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 39 publications
(88 reference statements)
1
14
0
Order By: Relevance
“…It is important to note that the amorphization depth found from the graph represented only the lower value of the real depth. For example, the model predicted that the amorphization depth was 23 nm for the fluence J/cm (see the line marked by the ▽ symbol), whereas the experiment showed it to be around 45 nm [ 19 ]. One reason for this discrepancy is the fact that we did not take into account the heat transport after the interaction.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that the amorphization depth found from the graph represented only the lower value of the real depth. For example, the model predicted that the amorphization depth was 23 nm for the fluence J/cm (see the line marked by the ▽ symbol), whereas the experiment showed it to be around 45 nm [ 19 ]. One reason for this discrepancy is the fact that we did not take into account the heat transport after the interaction.…”
Section: Theorymentioning
confidence: 99%
“…In addition, laser patterning can generate features with subwavelength resolution, as demonstrated by the production of highly periodic LIPPS with alternating -Si and c -Si regions [ 14 , 15 , 16 , 17 ]. -Si surrounded by c -Si can support waveguiding [ 18 ] and the research on the DLW integration of such devices was carried out in several studies [ 19 ]; however, the successful integration has yet to be demonstrated—the laser-produced -Si layer is too thin and prevents waveguiding for practical wavelengths. Using fluences well over the ablation threshold [ 20 ] or selecting the laser wavelength inside the silicon transparency window [ 19 ] still produces an amorphous layer of tens of nanometers in thickness.…”
Section: Introductionmentioning
confidence: 99%
“…The use of shorter laser pulses (pico-or femtosecond pulses) is characterized by high cooling rates (up to 10 12 Ks À1 ) [18] and hence, it is often used to disorder crystalline structures. [19,20] Nevertheless, ultrashort-pulsed (usp)-laser-induced crystallization of silicon layers and titanium oxides [21,22] are reported employing a pulse-to-pulse temperature accumulation effect. [23] For amorphous MoS 2 , a first-pulsed-laser-induced crystallization was reported, as a crystalline ring was formed during the processing with nanosecond Bessel beam pulses.…”
Section: Introductionmentioning
confidence: 99%
“…Methods for fabrication include chemical vapor deposition, [7][8][9] ion irradiation, [10,11] and laser irradiation. [12,13] Laser direct writing employs a pulsed laser source to modify the structure of Si resulting in the recrystallization or amorphization of c-Si, [14,15] which has attracted great attention from manufacturers and researchers due to its high precision and efficiency. [15] This technique relies on a wide variety of material changes induced by a high-intensity laser focused inside the bulk sample.…”
Section: Introductionmentioning
confidence: 99%